2014
DOI: 10.1152/japplphysiol.01084.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increase in tendon protein synthesis in response to insulin-like growth factor-I is preserved in elderly men

Abstract: Insulin-like growth factor-I (IGF-I) is known to be an anabolic factor in tendon, and the systemic levels are reduced with aging. However, it is uncertain how tendon fibroblasts are involved in tendon aging and how aging cells respond to IGF-I. The purpose of this study was to investigate the in vivo IGF-I stimulation of tendon protein synthesis in elderly compared with young men. We injected IGF-I in the patellar tendons of young (n = 11, 20-30 yr of age) and old (n = 11, 66-75 yr of age) men, and the acute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
0
33
1
1
Order By: Relevance
“…To further explore the difference in size between tendons of Scx:IGF1R + and Scx:IGF1R Δ mice, we determined whether IGF1 regulated general protein synthesis. IGF1 is known to activate the PI3K/Akt pathway, which increases protein synthesis in skeletal muscle (1), and local IGF1 can increase the protein fractional synthesis rate in tendons of elderly men and patients with Ehlers‐Danlos syndrome (13, 44). Using the SUnSET technique (20, 21), we observed that treating tenocytes with IGF1 doubled protein synthesis rates, and blocking Akt phosphorylation returned protein synthesis levels to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the difference in size between tendons of Scx:IGF1R + and Scx:IGF1R Δ mice, we determined whether IGF1 regulated general protein synthesis. IGF1 is known to activate the PI3K/Akt pathway, which increases protein synthesis in skeletal muscle (1), and local IGF1 can increase the protein fractional synthesis rate in tendons of elderly men and patients with Ehlers‐Danlos syndrome (13, 44). Using the SUnSET technique (20, 21), we observed that treating tenocytes with IGF1 doubled protein synthesis rates, and blocking Akt phosphorylation returned protein synthesis levels to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from in vitro studies of chondrocytes (Martin et al., ; Loeser et al., ) and in vivo study of osteoblasts (Cao et al., ) suggests that cells in older individuals have a reduced capacity to respond to IGF‐1. Recent work however has shown that local injection of IGF‐1 into the patellar tendon of young and old men is able to stimulate protein synthesis to an equal degree demonstrating that the ability to respond to anabolic stimuli is maintained in older age (Nielsen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐1 has been shown to have versatile roles in tissue engineering including mitotic and anabolic effects . Protein insulin is structurally analogous to IGF‐1 and has been shown to bind to IGF‐1 receptors to elicit similar effects yet is more widely available at lower costs than IGF‐1.…”
Section: Resultsmentioning
confidence: 99%
“…Mitotic effects of IGF‐1 in tendon cells and tendon animal models have also been well documented . IGF‐1 has also been observed to increase collagen synthesis . For example, injection of IGF‐1 was shown to increase collagen content near the injection site .…”
Section: Introductionmentioning
confidence: 99%